Social Media Training as a Tool for Branding and Promotion of MSMEs in Banjarsari Village - Olivine Alifaprilina Supriadi; Rully Sumarlin; Tiara Radinska Deanda (Pascasarjana Universitas Mataram, 2025)
This study examines the effectiveness of social media training as a tool for branding and promotion among MSMEs in Banjarsari Village, Garut. The training program involved workshops on managing Instagram and TikTok, developing engaging visual and textual content, and imple-menting digital advertising strategies tailored for rural MSMEs. Using a combination of pre- and post-training surveys, documentation anal-ysis, and participant observation, the research assesses changes in digital literacy, content production abilities, and commercial visibility. Findings reveal significant improvement in participants’ understanding and practical skills in social media branding, alongside increased con-fidence and creativity in content creation. This study demonstrates the important role of contextualized visual communication design educa-tion in supporting rural economic empowerment through digital trans-formation of MSMEs.